Risk of malnutrition in orthopedic trauma patients with surgical site infections is associated with increased morbidity and mortality – a 3-year follow-up study. Issue 10 (October 2020) - Maurer, Elke; Wallmeier, Vera; Reumann, Marie K.; Ehnert, Sabrina; Ihle, Christoph; Schreiner, Anna J.; Flesch, Ingo; Issack, Paul S.; Stollhof, Laura E.; Nüssler, Andreas K.
Highlights: 32.8% of all orthopedic trauma patients with surgical site infections (SSI) are at risk of malnutrition. Females have a higher risk of malnutrition than males. A risk of malnutrition is associated with an increased number of comorbidities and regular medication intake. Nutritional status does not impact on the readmission rate. Patients at risk of malnutrition have a 6.2-times higher mortality rate than well-nourished patients. Abstract: Background: Malnutrition is a worldwide problem which can result in prolonged hospitalization from complications such as poor wound healing and increased morbidity. There is increasing evidence of the effect of risk of malnutrition (ROM) on outcomes in orthopedic surgical patients. However, there is little data on the effect of nutritional status on clinical outcomes in orthopedic trauma patients with surgical site infections (SSI). Therefore, our aim was to investigate how malnutrition risk affects clinical outcomes in a prospective cohort of orthopedic trauma patients with SSI. Methods: The study included 345 patients who underwent surgery due to SSI at a level 1 trauma center. All patients were evaluated on their nutritional status as assessed by the Nutritional Risk Screening in 2014/15 and 2017/18. 238 (69.0%) datasets were available for the follow-up analysis. Twenty patients (8.4%) had died, resulting in 218 patients. Outcomes investigated included comorbidities, medication intake, destination of discharge, degree of mobility, support for procuring food, mortality risk and quality of life. Results: 32.8% were at risk of malnutrition (ROM) at EXAM1. Female patients had a higher ROM than males ( p  < 0.05). Patients with ROM had more comorbidities ( p  < 0.001), an increased need for medication intake ( p  < 0.001), a decreased level of mobility ( p  < 0.001) and increased need of support in procuring food ( p  < 0.001). The destination of discharge was independent of the nutritional status ( p  = 0.641). Twenty (8.4%) of the available 238 patients had died during follow-up time period, resulting in a 6.2-times higher risk of mortality in patients with ROM. EQ-5D revealed that mobility, self-supply and usual activities of daily living were increased in well-nourished patients ( p  < 0.001). Conclusion: ROM in orthopedic trauma patients with SSI is associated with an increased number of comorbidities and need for medication intake, a decrease in mobility and a higher dependency for food acquisition. Patients at ROM exhibited a 6.2-times higher mortality rate than well-nourished patients. EQ-5D evaluation showed better mobility, self-supply, and activity of daily living in well-nourished patients. We therefore strongly recommend supplementing patients with ROM with a specific diet during and after discharge from the hospital in order to reduce postoperative complications and long-term mortality.